Addressing Poverty in Industrial Zones: An Agile Governance and Zoning-Based Approach - Pratama, Inka Nusamuda; Zitri, Ilham; Azizah, Izmy Ratih (Universitas Muhammadiyah Yogyakarta, 2025)
This study examines the socio-economic conditions in Jereweh and Maluk Districts, industrial regions associated with PT. Amman Mineral Nusa Tenggara, focusing on the economic disparities among various community groups. The research aims to analyze these gaps and propose context-specific policies and poverty alleviation programs. Grounded in Agile Governance theory, which emphasizes Responsiveness, Adaptability, Collectivity, and Innovativeness, the study employs a qualitative methodology. Informants include the Regional Government, PT. Amman Mineral Nusa Tenggara, local communities, and NGOs, selected through purposive sampling. Data collection methods encompass observation, interviews, and documentation, while data analysis involves reduction, presentation, and conclusion drawing, supported by NVivo 12 Plus software. The findings reveal significant economic disparities within the communities of Jereweh and Maluk Districts, particularly among economically disadvantaged groups who have not fully benefited from the industrial activities. This has exacerbated economic inequality in the region. To address these issues, the study introduces a novel approach that integrates Agile Governance with a zoning system. It offers actionable policy recommendations, such as enhancing access to information, providing skills training, facilitating access to capital for micro, small, and medium enterprises (MSMEs), and strengthening community participation in decision-making processes. Additionally, the study proposes innovative solutions like the sharing economy and crowdfunding to foster inclusive economic growth. The insights and recommendations from this research provide practical guidance for stakeholders and can serve as a model for addressing similar challenges in other industrial areas. By combining theoretical frameworks with actionable strategies, this study contributes to the broader discourse on reducing economic inequality and promoting sustainable development in resource-rich but economically divided regions.